Rancang Bangun Mesin Buah Sortir Jeruk Berdasarkan Ukuran Standart Buah Jeruk dengan Kapasitas Penyortiran 500kg/Jam - Siregar, Chandra Amirsyah; Siregar, A M; Amri, Ahmad F; ., Zainal; ., Ramadhani; L, M Zulfadli (Rekayasa Material, Manufaktur dan Energi, 2024)
North Sumatra is a province that has a fairly extensive agricultural area. One of them is orange plants in the Besitang Sekoci plantation area, Langkat Regency and Karo Regency, North Sumatra Province. So, to support the quality of oranges, a sorting machine is needed that can guarantee the standardization of orange fruit, whether grade 1, 2, 3 and 4. In this research, an orange sorting machine will be designed and built. The sorting machine is designed and made using hollow iron measuring 40mm x 40mm, for the machine stand using UNP iron measuring 100 mm x 50 mm x 5 mm, the sorting or grade tube uses 12 inch paralon pipe, for the frame cover uses plate iron. with a thickness of 1.5mm, uses a conveyor as a distributor, uses an electric motor and gearbox connected to a pulley and belt to drive the machine. Before being built, the design results were also simulated using Solidworks software to determine the strength of the frame on the machine used and to obtain strong material quality when under load. From the simulation results, it is obtained that the machine design is safe to use. The orange fruit sorting machine is capable of sorting fruit according to size standards based on SNI 3165-2009 with a capacity of 500kg/hour.